KONSEP PENDIDIKAN PESANTREN MENURUT K.H ABDULLAH SYUKRI ZARKASYI DAN RELEVANSINYA BAGI PENGEMBANGAN PENDIDIKAN ISLAM DI INDONESIA - Qodari, Imam; Happy Susanto; Much. Tajab (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This study uses Library Research. The data presented in this study are taken from written materials in the form of books, journals and others related to the discussion. Among the data sources are the works of K.H. Abdullah Syukri Zarkasyi. The method or technique of data collection is using documentary techniques. The results of the study show that the education initiated by K.H. Abdullah Syukri Zarkasyi is based on the values ​​and philosophy of life of the Darussalam Gontor Modern Islamic Boarding School contained in the Panca Jiwa. The Panca Jiwa are five things that are the philosophy of life of all residents of the Darussalam Gontor Modern Islamic Boarding School in carrying out education and teaching. The Panca Jiwa consists of Sincerity, Simplicity, Self-Reliance, Islamic Brotherhood, and Freedom. According to K.H. Abdullah Syukri Zarkasyi, Education is everything or all of what we see, what we hear, and what we feel in the Islamic boarding school. The meaning is that everything we do in the Islamic boarding school has educational value. Regarding its relevance to Islamic education in Indonesia, K.H. Abdullah Syukri Zarkasyi's educational concept has had a significant influence on the development of Islamic education in Indonesia. The development of the Islamic boarding schools he led into rapidly expanding Islamic boarding schools (pesantren) is evidence that his concept and system of Islamic boarding school education were accepted and considered good by Indonesian society.